Density And Permeability Properties Of Over Compacted Sands And Laterites - Ng, Chun Hua (Universiti Sains Malaysia, 2018)
Proper soil compaction is essential in any type of construction project. It is very important because it provides the necessary platform that will sustain the crucial support for the buildings, various construction foundations, landfills, and any other construction structures. Therefore, soil compaction have to be applied sufficiently and practically with the concern to the aspect of the desired soil parameters, yet taking consideration to the time and cost of the entire compaction process. This dissertation presents the relationship between the 3 major parameters, which are the dry density gained, the permeability coefficient reduced and the compaction energy applied to the soil. Laterite soil and river sand are the two of the most abundant soil materials present in construction field were chosen as the soil sample for this research study. The soil samples have undergone permeability and proctor compaction tests with different level of compaction energy to acquire sufficient data for the analysis and interpretation of the relationship between the 3 major parameters. Proctor compaction tests were conducted at first as the results of the data are required to use as the constant variables in the permeability test later. The results show that the laterite soil have greater sensitive to the change of compaction energy in term of the dry density and permeability coefficient that are affected. Besides that, laterite soil shows properties with higher maximum dry density and lower permeability coefficient obtained from the same compaction energy with the river sand. However, although the laterite soil show lower permeability coefficient as compared to the river sand, both of the soil samples are still far beyond from the impervious permeability properties that are required for landfill purpose. The optimum compaction energy for dry density and permeability purpose are different and it varies with type of soil sample. Last but not least, the findings from this research provides useful information for the engineer to estimate the suitable compaction energy that are required for their construction project.